Quality of life and patient satisfaction with outpatient care after heart transplantation in adult and pediatric patients – room for improvement?. (5th November 2021) - Schmithausen, Alexander; Tengler, Anja; Birnbaum, Julia; Haas, Nikolaus A.; Rosenthal, Laura L.; Orban, Madeleine; Hagl, Christian; Dalla Pozza, Robert; Jakob, Andre; Fischer, Marcus; Ulrich, Sarah M.
Summary: Reduced adherence after heart transplantation increases the risk for acute rejection. Therefore, the aim of this study was to evaluate the patient's satisfaction with outpatient care and quality of life (QOL) after pediatric and adult heart transplantation. Observational study after pediatric ( n  = 22) and adult ( n  = 65) heart transplantation and the parents of the pediatric patients ( n  = 22) to evaluate the patients' satisfaction with outpatient care and QOL. Established standardized questionnaires were used for patient satisfaction (ZAP survey) and QOL (SF36); the latter was compared with the cohort of the BGS98 survey (BGS98 cohort). ZAP score: excellent results with almost all values >80. QOL: pediatric cohort showed significantly higher values in physical functioning ( P  = 0.041) and role physical ( P  = 0.003) but significantly lower values in the sub‐scale general health ( P  = 0.02) compared to adult cohort. In comparison with BGS98 cohort, children showed almost similar results, whereas adult cohort showed worse values in physical and emotional functioning, but higher values regarding general health. The QOL of patients after pediatric heart transplantation is comparable to a standardized reference population in Germany, whereas adult patients show reduced physical and emotional functioning, but better values regarding general health. The patients' satisfaction with the outpatient care is very high. Abstract : The patient satisfaction with outpatient care is high after heart transplantation in Germany. The quality of life of patients after pediatric heart transplantation is comparable with a standardized German population. Patients after adult heart transplantation show reduced physical and emotional functioning.